Being not in One's Own Will, or On the Need for Academic Autonomy - E. N. Roshchin; E. B. Potapova (Теоретическая и прикладная юриспруденция)
This article is an analytical review on the question of academic freedom. The main focus of the article is on the idea of academic autonomy as an institutional mechanism which guarantees individual academic freedom. The theme of universities’ autonomy is becoming increasingly prevalent in global discussions, as the role of universities is volving. The process of internationalization of higher education, requirements for universities’ efficiency, transformation of state control and funding have significant influence on the status of universities in the society. Current research shows that this new status, together with perspectives of development lead to the increasing dependency of universities on various stakeholders. These core stakeholders, influencing autonomy are the state, business, and students as customers. Growing dependency on the private interest in turn leads to the erosion of importance that society assigns to the university as an institution.